The effects of geriatric oral dental health training to dental students on their elderly attitudes - Hastaoglu, Fatma (Journal of the Pakistan Medical Association, 2024)
Objective: To measure the effect of geriatric oral health education on the attitude of dentistry students towards the elderly. Methods: The interventional study was conducted in December 2022 at Sivas, and comprised students of the Faculty of Dentistry, Sivas Cumhuriyet University, Turkiye in their 4th and 5th academic year. A 20-hour training course was delivered over 3 days by faculty members. Baseline and post-intervention difference was assessed using the Kogan’s Attitudes Towards Old People Scale. Data was analysed using SPSS 22. Results: Of the 30 students, 18(60%) were females and 12(40%) were males. The overall mean age was 22.93±1.63 years. Besides, 18(60%) students belonged to 5th year and 12(40%) to the 4th year. The mean Kogan Elderly Attitude Scale score at baseline was 184.13±25.55, while post-intervention it was 195.36±22.36. (p<0.05). Conclusion: Relevant training was found to have a significant impact on the attitude of dentistry students towards the elderly. Key Words: Oral health, Dentistry, Aged, Attitude, Health education.